CREATING GUIDANCE FOR THE USE OF PATIENT REPORTED OUTCOME MEASURES (PROMS) IN CLINICAL PALLIATIVE CARE. Issue 1 (1st March 2014) - van Vliet, LM; Harding, R; Bausewein, C; Payne, S; Higginson, IJ; ,
Abstract : Introduction: Routine use of Patient Reported Outcome Measures (PROMs) in clinical practice can influence care but is not always achieved. One reason for this seems to be a lack of guidance on how to use PROMs in palliative care practice. This project aimed to provide such guidance. Aim(s) and method(s): The 8-steps of implementing PROMs in clinical practice proposed by the International Society for Quality of Life Research were used as a framework. Recommendations within each step were created based on several sources including the booklet 'Outcome Measures in Palliative Care: The Essentials' and the EAPC White paper Outcome Measures. Results: For the following steps, recommendations (including the provided examples) were created: i) identify the goals for collecting PROMs (e.g. screening versus monitoring of changes); ii) select patients, setting and timing of assessment (e.g. assess families' own needs); iii) determine which questionnaire to use (e.g. choose questionnaire based on evidence); iv) choose a mode for administering/scoring the questionnaire (e.g. self-administration versus computer-administration); v) design processes for reporting results (e.g. share results with patient/practitioners); vi) identify aids to facilitate score interpretation (e.g. determine the minimum clinically important difference); vii) develop strategies for responding to identified issues (e.g. integrate PROM data with other clinical data); viii) evaluate the impact of measuring PROMs on practice (e.g. conduct benchmarking). Conclusion(s): As PROMs are increasingly used in palliative care, the proposed guidance is essential and timely. Future work will integrate this guidance with more questionnaire-specific guidance to optimise its usability and impact in clinical care.